Landslide ecology - Walker, Lawrence R. (Ecology, biodiversity, and conservation.)
"Despite their often dangerous and unpredictable nature, landslides provide fascinating templates for studying how soil organisms, plants, and animals respond to such destruction. The emerging field of landslide ecology helps us to understand these responses, aiding slope stabilization and restoration and contributing to progress made in geological approaches to landslide prediction and mitigation. Summarizing the growing body of literature on the ecological consequences of landslides, this book provides a framework for the promotion of ecological tools in predicting, stabilizing, and restoring biodiversity to landslide scars at both local and landscape scales. It explores nutrient cycling; soil development; and how soil organisms disperse, colonize, and interact in what is often an inhospitable environment. Recognizing the role that these processes play in providing solutions to the problem of unstable slopes, the authors present ecological approaches as useful, economical, and resilient supplements to landslide management"--